Coach. Mentor. Assistant. iPhone. - Stern, Zack.
Your iPhone or iPod touch is an entertainer, communicator, and some might even say friend. And while it's OK to harbor such warm and fuzzy feelings--as long as you don't try to make out with it--your device can also crack virtual whip to well, make you a better person. With the right apps, you can turn it into a drill sergeant, teacher, and personal assistant. Whether you're expanding your horizons for New Year's resolutions or just catching up on old goals, the iPhone can be your guide. We've picked our favorite apps to help improve your health and organization. Be a better biker, task manager, and more. We've also selected great apps to teach you new things and introduce hobbies. Pick and choose apps of interest, or just dive into our full list. Whatever your approach, we have a new title for the iPhone : Life Coach.
Keywords: Nike + Sensor; iPhone applications; iPod Touch; iPhone